The Formation Of Misty Band Near The Substrate During Contact Angle Measurement - Linli Wu (The Minerals, Metals and Materials Society, 2006)
During the measurement of contact angle, a misty band was observed near the substrate. Hsien-Nan Ho and Shinn-Tyan Wu thought this was because the oxygen atoms on the interface migrate to the droplet surface to form an oxide band near the substrate. But from our experiments misty band appeared before the drop reach to the substrate. Theoretically speaking, the oxygen partial was the same everywhere in the vacuum furnace. So there was no condition to provide enough oxygen forming oxide. This appearance would be explained more reasonably with the optics principle. Most reflected light would be absorbed by the substrate and the light cannot reach the observation area, so the misty band formed.